Stress Makes the Difference: Social Stress and Social Anxiety in Decision-Making Under Uncertainty - Hengen, Kristina M.; Alpers, Georg W. (Frontiers in Psychology, 2021)
Stress and anxiety can both influence risk taking and decision making. While stress typically increases risk taking, anxiety often leads to more risk-averse choices. Few studies have examined both aspects in one paradigm. We therefore set out to examine emotional decision making under stress in socially anxious participants. In our study, individuals (N = 87) high or low in social anxiety completed a variation of the Balloon Analogue Risk Task (BART). While pumping up a balloon larger is rewarded, a possible explosion leads to a) loss of money and b) it is followed by an emotional picture (i.e., a calm or an angry face). To induce stress, participants were told that they will have to deliver a speech. We operationalized risk taking by the number of pumps and its functionality by the amount of monetary gain. In addition, response times were recorded as an index of decisional conflict. Without the stressor, high socially anxious compared to low socially anxious participants did not differ in any of the dependent variables. However, under stress, high socially anxious individuals were more risk averse, earned less money, and made their decisions more hesitantly. Unexpectedly, there were no main effects or interactions with the valence of the faces. This data shows that stress differently affects socially anxious individuals: Low socially anxious individuals increase risk taking under stress whereas highly socially anxious individuals maintained a defensive strategy. The novel eBART is a promising research tool to examine the specific factors that influence decision making.